URGENSI SERTIFIKASI JULEHA DAN SISTEM TIMBANG TERHADAP TINGKAT PENJUALAN KAMBING AKIKAH - Arief; Muhammad Irwan Padli Nasution; Andri Soemitra (CV. Lafadz Jaya, 2026)
Indonesia's large Muslim population and the increasing demand for aqiqah goats. To ensure that goats are slaughtered according to Islamic law, JULEHA is needed. JULEHA certification is crucial because it provides assurance to consumers that the meat they consume has been slaughtered according to halal standards. The importance of JULEHA certification in the aqiqah goat slaughtering business aims to ensure that the slaughtering process is in accordance with Islamic law and supports business sustainability and guarantees that the goat meat has been processed according to halal standards. JULEHA certification can improve product quality, maintain halal standards, and increase consumer trust in aqiqah goat sales outlets. The sale of aqiqah goats is also required to comply with the principles of fairness and transparency, namely by using a kilo weighing system by multiplying the live weight of the goat by the agreed price per kilogram. This research is expected to contribute to the understanding of the importance of JULEHA certification and weighing system by aqiqah goat sales businesses. The author employed field research with a qualitative approach to gain a deeper understanding of the importance of JULEHA certification and the weighing system for the sale of akikah goats. The data sources used in this study were primary and secondary. Data collection techniques included interviews, observations, and documentation in Asahan Regency. The results indicate that JULEHA certification and the weighing system for the sale of akikah goats can increase sales, consumer confidence, and support business sustainability.